Trabajo Social de ciclo largo, medio y corto: distintos ritmos de un mismo caminar - Hernández, M.ª Dolores (Cuadernos de Trabajo Social, 2006)
This article proposes a way of practicing community social work based on the participation of the population in the process of reflection and action for change. Participation must be the focus in all of the methodological steps, from the proposal to the evaluation, allowing the population to decide what aspects to work on or to determine what objectives to pursue. It seeks to make the population a protagonist in the process and puts forth the role of social worker as a guide, above all, motivating, analyzing the relationships, especially those related to power.
Keywords: Community Social Work; Citizen participation; Social networks; Power